Feedback Literacy as a Dimension of Teacher Professional Development: Exploring in Service Teachers’ Capacity to Seek, Interpret, and Use Feedback - Effendi Limbong (Barkah Publishing, 2026)
Feedback literacy has emerged as a significant construct in higher education research, yet its application to in‑service teachers’ professional learning remains underexplored. This study investigates how practising secondary teachers seek, interpret, and use feedback within their everyday professional contexts, and how these capacities contribute to their professional growth. Drawing on interpretive phenomenological analysis (IPA), semi‑structured interviews were conducted with 12 in‑service secondary teachers (3–10 years’ experience) across three phases: narrative elicitation, critical incident reflection, and longitudinal follow‑up. Analysis yielded three superordinate themes: (1) “making feedback actionable” – describing the interpretive work required to translate evaluative comments into pedagogical adjustments; (2) “relational conditions for seeking feedback” – highlighting trust, vulnerability and collegial safety as prerequisites for proactive feedback engagement; and (3) “feedback as reflective fuel” – revealing how feedback loops sustain or disrupt teachers’ professional noticing and self‑directed improvement. Findings extend Carless and Boud’s (2018) feedback literacy framework from student to teacher professional contexts, proposing that teacher feedback literacy comprises four intersecting capacities: evaluative discernment, relational positioning, temporal integration, and self‑regulatory agency. The study contributes to professional development literature by demonstrating that feedback literacy is not merely a skill to be taught, but a relational and dispositional capacity that develops through sustained opportunities for dialogic engagement with multiple feedback sources. Implications for continuing professional development design include structured feedback dialogue protocols, peer observation with interpretive scaffolding, and institutional cultures that normalise feedback‑seeking as professional practice rather than deficit remediation.